PBL Dissemination: Introduction of RABAL Probiotic to Livestock Farmers in Cibal Village, Manggarai District, NTT Province - Dedy Dorens Mesak; Familianus Fourenal; Stormy Vertygo (Universitas Serang Raya, 2026)
The livestock subsector in East Nusa Tenggara (NTT) contributes 28.51% to the regional GDP and employs 51.4% of the workforce; however, its economic growth remains slow, ranking only seventh among 17 economic sectors. One of the primary causes of this slow growth is low livestock productivity, which is largely attributed to poor feed processing practices that limit nutrient absorption and result in suboptimal average daily weight gain in cattle. To address this root cause, students at Politeknik Pertanian Negeri Kupang introduced Rabal Probiotics to farmers in Rado Village through the Student Community Service Program (KKBM). Rabal Probiotics, a locally developed probiotic containing Saccharomyces cerevisiae and Lactobacillus casei, improves feed digestion and nutrient absorption, thereby directly enhancing livestock growth rates. The students conducted training activities comprising lectures, demonstrations, and hands-on practice to increase farmers' understanding and practical skills in producing Rabal Probiotics, promote sustainable livestock practices, and demonstrate successful project-based learning implementation. The results showed that all participating farmers (100%) mastered the theoretical aspects, while practical understanding of proportional scaling increased to 70%.